Enduring authoritarianism, endemic instability, and elusive peace in Sudan - Ylönen, A.; Zahorik, J. (The Horn of Africa since 2018: Continuities, transformations, and prospects, 2025)
Since Sudan's independence, political instability has been endemic, resulting in frequent regime changes and protracted repression and violence. Although political instability and regime transitions in Sudan have received considerable attention in the scholarly literature, they have rarely been discussed from the perspective of continuity of authoritarian rule. This chapter explains the enduring authoritarianism in Sudan and the related endemic political instability and elusive peace. It maps the trajectory of conflict and political instability in the country and discusses the major determinants of elusive peace and endemic instability to better understand the linkages between enduring authoritarianism, political instability, and violent conflict. The last part of the chapter deals with various external factors that contribute to protracted political turbulence in Sudan. Therefore, this chapter argues that a sustained political transition from enduring authoritarianism toward democracy requires both continued commitment to lasting internal political transformation and significant lessening of the disruptive external involvement.